Prospects for the introduction of innovative types of advertising in tourism (Economics and region, 2023)
Advertising has an important position in the process of providing tourist services and in the conditions of competition. It contributes to the increase of the company's popularity, the number of customers and the company's income. The article reveals the essence of advertising, its functions, principles of its implementation. Factors influencing the advertising activity of a tourist enterprise are given. The Ukrainian advertising market was negatively affected by the war in Ukraine. In particular, the advertising market fell by 63% in 2022 compared with 2021. The biggest decline was in TV and press advertising. At the same time, the role of internet advertising is growing, with a share of 58.8% in 2022. Innovative forms of advertising that are creative and interesting to consumers will become increasingly important. The latest innovations in advertising that can be used in the tourism industry include InDoor TV technology, interactive table, Ground FX technology, TransLook (transparent kiosk), Just Touch interactive technology, projection advertising, non-disappearing advertising, QR codes and others. The problems with the implementation of innovative forms of advertising are their sometimes high costs and the impossibility of accurately predicting how they will affect consumers. The article discusses social marketing tools, which are also becoming increasingly popular. The benefits of their use for companies are highlighted: wide and more accurate coverage of the target audience; increased brand awareness; rapid feedback from customers; increased loyalty of potential buyers; less time spent creating and maintaining a group in a social network; prompt notification of customers about new offers; relatively low cost of promotion; feedback can be tracked; variety of forms of submission. The main types of advertising in social networks are revealed: contextual, targeting, teaser, retargeting advertising, work with bloggers. It was found that the most popular social networks among Ukrainians are Facebook, Instagram, YouTube and TikTok. An obstacle to the implementation of social marketing tools is the inability of employees to use them, while at the same time they give a good result, contribute to the increase in the number of customers and profits.
Keywords: advertising; innovation; social media; contextual advertising; targeting; teaser advertising; retargeting; video marketing; blogging; branding